2013
DOI: 10.2135/cropsci2011.06.0306
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Grass and Legume Species as Perennial Ground Covers in Corn Production

Abstract: Corn (Zea mays L.) stover has been identified as an important feedstock for biofuel production but its removal will likely increase soil erosion. To address this issue 35 species of grasses and legumes were evaluated as potential perennial ground covers (PGCs) in corn. Selection of species encompassed both C3 and C4 species with a wide range of developmental and morphological features. The objectives were to (i) identify species that could support a high level of corn production while requiring minimal managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 19 publications
7
40
0
Order By: Relevance
“…These findings are consistent with earlier reports, which found that consistent and uniform maize stands in maize-sod systems were challenging to achieve (Stanley and Gallaher, 1980), observed delayed maturity in intercropped maize (Kloeke et al, 1989) and reported that greater LM cover generally resulted in lower maize plant density than the control (Flynn et al, 2013). Observed reductions in plant density in the no LM treatment maize with residue retention versus no LM treatment maize with residue removal are consistent with other reports regarding lower emergence rates for maize treatments with residue retention across various tillage methods (Dam et al, 2005) and reduced maize plant growth when the maize plant was in close proximity to residue (Yakle and Cruse, 1983).…”
Section: Maize Maturity and Plant Densitysupporting
confidence: 93%
See 4 more Smart Citations
“…These findings are consistent with earlier reports, which found that consistent and uniform maize stands in maize-sod systems were challenging to achieve (Stanley and Gallaher, 1980), observed delayed maturity in intercropped maize (Kloeke et al, 1989) and reported that greater LM cover generally resulted in lower maize plant density than the control (Flynn et al, 2013). Observed reductions in plant density in the no LM treatment maize with residue retention versus no LM treatment maize with residue removal are consistent with other reports regarding lower emergence rates for maize treatments with residue retention across various tillage methods (Dam et al, 2005) and reduced maize plant growth when the maize plant was in close proximity to residue (Yakle and Cruse, 1983).…”
Section: Maize Maturity and Plant Densitysupporting
confidence: 93%
“…The maize grain yield reduction for LM treatment maize is similar to other reports in that excessive competition from LM resulted in lower grain yield than conventional maize (Adams et al, 1970;Carreker et al, 1972;Robertson et al, 1976;Flynn et al, 2013). In the SM sequence at Boone, the yield-stable hybrid produced greater total aboveground biomass in no LM treatments than LM treatments, at 20.20 and 14.33 Mg ha −1 , respectively.…”
Section: Maize Total Aboveground Biomass Stover Yield Grain Yield supporting
confidence: 83%
See 3 more Smart Citations